Access to the healthcare system: Experiences and perspectives of Pakistani immigrant mothers in New Zealand - Sumera Saeed Akhtar; Susan Heydon; Pauline Norris (Elsevier, 2022)
Worldwide, there is limited literature on Pakistani immigrants' challenges and experiences accessing healthcare services for their children and themselves. In this article, we present a case study of Pakistani immigrant mothers in New Zealand to explore their experiences and perspectives on navigating the healthcare system of a new country. Data was collected from 23 mothers in Wellington through in-depth semi-structured interviews, which each lasted 60 to 80 min. Participants had been living in New Zealand for an average of 3.25 years and were mostly highly educated. They talked about their prior knowledge and experiences regarding the New Zealand healthcare system. Lack of knowledge, different expectations, and experiences of healthcare services inhibited their utilization of healthcare. Most mothers treated their children at home before visiting a general practitioner (GP) due to previous perceived unsatisfactory experiences, such as lack of availability of GP appointments for the same or next day, or long waiting times at emergency departments and after hours medical facilities. Immigrant mothers need to feel they are getting the right services at the right time to ensure and promote better health outcomes. Identifying the barriers and promoting information about the healthcare system can play an essential role in the appropriate use of health services by immigrant mothers.